Archaeal S-Layers: Overview and Current State of the Art - Rodrigues-Oliveira, Thiago; Belmok, Aline; Vasconcellos, Deborah; Schuster, Bernhard; Kyaw, Cynthia M. (Frontiers in Microbiology, 2017)
In constrast to bacteria, all archaea possess cell walls lacking peptidoglycan and a number of different cell envelope components have also been described. A paracrystalline protein surface layer, commonly referred to as S-layer, is present in nearly all archaea described to date. S-layers are composed of only one or two proteins and form different lattice structures. In this review, we summarise current understanding of archaeal S-layer proteins, discussing topics such as structure, lattice type distribution among archaeal phyla and glycosylation. The hexagonal lattice type is dominant within the phylum Euryarchaeota, while in the Crenarchaeota this feature is mainly associated with specific orders. S-layers exclusive to the Crenarchaeota have also been described, which are composed of two proteins. Information regarding S-layers in the remaining archaeal phyla is limited, mainly due to organism description through only culture-independent methods. Despite the numerous applied studies using bacterial S-layers, few reports have employed archaea as a study model. As such, archaeal S-layers represent an area for exploration in both basic and applied research.